Association between life’s essential 8 and bone mineral density among adults aged 20–59 years - Yuyu Cui; Zhening Xu; Zhaoshu Cui; Yuanyuan Guo; Peiwei Wu; Xiaoyan Zhou (Scientific Reports)
Abstract This study investigates the relationship between Life’s Essential 8 (LE8) scores and bone mineral density (BMD) in adults aged 20–59 years. This cross-sectional analysis employed nationally representative data from NHANES 2011–2018. Weighted multiple linear regression models were applied to assess the association between LE8 scores and varying levels of cardiovascular health (CVH) with BMD. Subgroup analyses were performed to evaluate differences in the impact of LE8 scores on BMD across age groups, genders, races, socioeconomic statuses, and BMI categories. The study included 2159 participants. After adjusting for all covariates, LE8 scores demonstrated a significant positive linear association with lumbar spine BMD, thoracic spine BMD, trunk BMD, and total BMD. Individuals in the medium and high CVH groups exhibited higher BMD compared to those in the low CVH group. Subgroup analyses indicated that the association was more evident in participants aged 20–35 years and among those with normal BMI. In females, thoracic spine BMD appeared particularly sensitive to changes in LE8 scores. This study identifies a positive linear relationship between LE8 scores and BMD. Higher CVH scores were linked to greater BMD in adults aged 20–59 years. These findings highlight the importance of adopting comprehensive health strategies, suggesting that improving CVH may contribute to maintaining bone density and supporting skeletal health.